2005
DOI: 10.1103/physrevlett.95.173001
|View full text |Cite
|
Sign up to set email alerts
|

Origins of Nonexponential Decay in Single Molecule Measurements of Rotational Dynamics

Abstract: Recent reports have demonstrated that the correlation function of the fluorescence dichroism signal, measured as a probe of single molecule rotational dynamics, should not manifest a single exponential decay even for isotropic diffusion. This has called into question the attribution of observed nonexponential behavior in supercooled fluids and polymer systems to dynamical heterogeneity. We show here that, for the case of a high numerical aperture objective, the dichroism decay becomes indistinguishable from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 14 publications
1
79
1
1
Order By: Relevance
“…As for the ensemble, we fitted a single exponential to the autocorrelation function C A Ј(t) of the lineardichroism time trace to obtain the tumbling time in the given † A possible source of nonexponentiality is the nonspherical shape of the molecule. Wei et al (35) have shown that the associated high-order contributions to the correlation function are much reduced by collection over a finite solid angle and are therefore negligible in practice.…”
Section: Methodsmentioning
confidence: 99%
“…As for the ensemble, we fitted a single exponential to the autocorrelation function C A Ј(t) of the lineardichroism time trace to obtain the tumbling time in the given † A possible source of nonexponentiality is the nonspherical shape of the molecule. Wei et al (35) have shown that the associated high-order contributions to the correlation function are much reduced by collection over a finite solid angle and are therefore negligible in practice.…”
Section: Methodsmentioning
confidence: 99%
“…[54][55] Fisz et al 54 and Wei et al 55 have discussed a detailed procedure for taking in account of this. However, for the sake of simplicity, we have used equation (1) as an approximation.…”
Section: Picosecond Time-resolved Fluorescence Decays Under a Micrmentioning
confidence: 98%
“…For a number of years, researchers have attempted to monitor relaxation processes in glass formers by embedding a single dye molecule in a polymer of interest. [90][91][92][93][94][95] The idea is that small rotational motions of the embedded dye would be able to report back on the relaxation process of the polymer under investigation. Several microscopy techniques have been developed over the last years to monitor the rotational motion of single molecules in three dimensions.…”
Section: Following Polymer Dynamics Near the Glass-transitionmentioning
confidence: 99%